Reconsidering Retrieval Effects on Adult Regularization of Inconsistent Variation in Language. Issue 4 (2nd October 2019) - Hudson Kam, Carla L.
ABSTRACT: The phenomenon of regularization – learners imposing systematicity on inconsistent variation in language input – is complex. Studies show that children are more likely to regularize than adults, but adults will also regularize under certain circumstances. Exactly why we see the pattern of behaviour that we do is not well understood, however. This paper reports on an experiment investigating whether it is possible to induce regularization in adults by varying the conditions of learning and/or testing in ways that made retrieval more difficult, something predicted by previous studies of regularization. The data show that interfering with learning does not lead to regularization, but that interfering with retrieval at test does, although only to a small degree.